Association between Patients’ Self-Judgement, Coagulated Menstrual Blood, and Menorrhagia: Results from a Questionnaire Survey and Blood Test Analysis - Eun Ji Lee; Ji Eun Ahn; Jung Min Ryu; Yoon Young Jeong; Youn Seok Choi (Medicina, 2023)
Background and Objectives: Menorrhagia is defined as a blood loss of more than 80 mL, which is significant enough to cause anemia. Previously known methods for evaluating menorrhagia, such as the alkalin-hematin method, pictograms, and measuring the weight of sanitary products, were all impractical, complex, and time-consuming. Therefore, this study aimed to determine which item among menstrual history taking was most associated with menorrhagia and devised a simple evaluating method for menorrhagia through history taking that can be applied clinically. Materials and Methods: The study was conducted from June 2019 to December 2021. A survey was conducted on premenopausal women who underwent outpatient treatment or surgery and those who underwent a gynecologic screening test, and their blood tests were analyzed. The presence of iron deficiency anemia was identified with a Hb level of less than 10 g/dL with microcytic hypochromic anemia on a complete blood count performed within one month of the survey. A questionnaire survey was conducted on six items related to menorrhagia to investigate whether each item was related to “significant menorrhagia”. Results: There were 301 participants in the survey during the period. In univariate analysis, the results revealed a statistically significant association between significant menorrhagia and the following items: self-judgement of menorrhagia; menstruation lasting over 7 days; total pad counts in a single menstrual period; Number of sanitary products changed per day; and leakaging of menstrual blood and presence of coagulated menstrual blood. In multivariate analysis, only the “self-judgement of menorrhagia” item showed a statistically significant result (p-value = 0.035; an odds ratio = 2.217). When the “self-judgement of menorrhagia” item was excluded, the “passage of clots larger than one inch in diameter” item showed a statistically significant result (p-value = 0.023; an odds ratio = 2.113). Conclusions: “Patient self-judgement of menorrhagia” is a reliable item for evaluating menorrhagia. Among several symptoms indicating menorrhagia, determining the presence of the “passage of clots larger than one inch in diameter” during the menstrual period is the most useful item for evaluating menorrhagia in clinical history taking. This study suggested using these simple menstrual history taking items to evaluate menorrhagia in real clinical practice.